Requirement of NF-kappa B Activation in Different Mice Brain Areas during Long-Term Memory Consolidation in Two Contextual One-Trial Tasks with Opposing Valences - Salles, Angeles; Krawczyk, Maria del C.; Blake, Mariano; Romano, Arturo; Boccia, Mariano M.; Freudenthal, Ramiro (Frontiers in Molecular Neuroscience, 2017)
NF-kappa B is a transcription factor whose activation has been shown to be necessary for long-term memory consolidation in several species. NF-kappa B is activated and translocates to the nucleus of cells in a specific temporal window during consolidation. Our work focuses on a one trial learning tasks associated to the inhibitory avoidance (IA) setting. Mice were trained either receiving or not a footshock when entering a dark compartment (aversive vs. appetitive learning). Regardless of training condition (appetitive or aversive), latencies to step-through during testing were significantly different to those measured during training. Additionally, these testing latencies were also different from those of a control group that only received a shock unrelated to context. Moreover, nuclear NF-kappa B DNA-binding activity was augmented in the aversive and the appetitive tasks when compared with control and naïve animals. NF-kappa B inhibition by Sulfasalazine injected either in the Hippocampus, Amygdala or Nucleus accumbens immediately after training was able to impair retention in both training versions. Our results suggest that NF-kappa B is a critical molecular step, in different brain areas on memory consolidation. This was the case for both the IA task and also the modified version of the same task were the footshock was omitted during training. This work aims to further investigate how appetitive and aversive memories are consolidated.